Regulação de miRNAS em gemas de Coffea arabica com aplicação de 1-MCP em diferentes condições hídricas - Garcia, Bruno de Oliveira (2019)
Coffee is a commodity with great economic importance in the world. The coffee production chain generates millions of jobs in various segments. Several cultivars have already been developed aiming at the production’s improvement, but the asynchronous flowering is a problem for the culture. Asynchrony causes uneven maturation of the fruits, which affects the final quality of the product. Unlike most plants that emit inflorescences during the spring and fructify within the same phenological year, Arabica coffee (Coffea Arabica L.) is a biannual species and takes two years to complete its reproductive cycle. The floral induction period occurs in the first phenological year with the formation and development of the floral buds. After completing their development, these buds fall into dormancy and become ready for anthesis, which occurs when there is a substantial increase in water potential, a phenomenon that can be induced by episodes of rain or scheduled irrigation. MicroRNAs (miRNAs) have been prominent in studies where they appear as key regulators of response to phytohormones pathways in plants, affecting their metabolism, distribution, and perception. The flowering of the coffee tree is not controlled by an isolated factor. This process is influenced by the action of different phytohormones and miRNAs, which interact in a complex regulation network. Ethylene is a phytohormone involved in several morphophysiological processes, being related to responses to abiotic stress. In relation to the flowering, the ethylene can inhibit or induce anthesis in different species. In coffee trees, the use of an ethylene action inhibitor, 1- methylcyclopropene (1-MCP) was able to promote the anthesis in flowers after a period of water restriction. miRNAs are involved in several phases of the plant development, acting as regulators of gene expression at the post-transcriptional level. The miRNAs act by regulating the gene expression in several stages of the plant development, including anthesis, and are able to establish a communication with phytohormones. In order to investigate the participation of miRNAs in the coffee flowering process, and the possible interaction of them with the inhibition of ethylene action, this study aimed to evaluate the effect of the application of 1-MCP on the expression of potentially responsive miRNAs in coffee buds under different water conditions. Therefore, miRNAs miR157, miR395, miR396, and their respective targets, SPL2, SULTR2;1 and GsSRK, were selected for analysis of gene expression by stem-loop RT-PCR. The results of the RT-qPCR experiments showed that in plants under water stress, only miR157a-5p was responsive to the application of 1-MCP. In the case of reirrigated plants miR395a-3p showed lower expression than the control, and miR396a-3p was more expressed for this same condition. Regarding the targets, no differential expression was observed for any of the treatments. For plants that did not undergo water deficit, there was no difference in the expression for the three miRNAs. The results demonstrate that the miRNAs participate in the breakage or maintenance of the coffee bud dormancy depending on the water availability or the 1-MCP application.